If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 5(x + -12) = 5(x + -10) Reorder the terms: 5x + 5(-12 + x) = 5(x + -10) 5x + (-12 * 5 + x * 5) = 5(x + -10) 5x + (-60 + 5x) = 5(x + -10) Reorder the terms: -60 + 5x + 5x = 5(x + -10) Combine like terms: 5x + 5x = 10x -60 + 10x = 5(x + -10) Reorder the terms: -60 + 10x = 5(-10 + x) -60 + 10x = (-10 * 5 + x * 5) -60 + 10x = (-50 + 5x) Solving -60 + 10x = -50 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -60 + 10x + -5x = -50 + 5x + -5x Combine like terms: 10x + -5x = 5x -60 + 5x = -50 + 5x + -5x Combine like terms: 5x + -5x = 0 -60 + 5x = -50 + 0 -60 + 5x = -50 Add '60' to each side of the equation. -60 + 60 + 5x = -50 + 60 Combine like terms: -60 + 60 = 0 0 + 5x = -50 + 60 5x = -50 + 60 Combine like terms: -50 + 60 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| 4x^3-20x^2-68x+84=0 | | 13+7x=2x-12 | | -192=5x+2(4x-18) | | -32-8x=49-11x | | -3x+86=-114+5x | | 14+2n=2-n | | 110=-5x+2(-x+13) | | 110=-5x+2 | | 46-y+10y=136 | | 3x-3(5x+10)=42 | | 10x+6y=72 | | 92-2x=25x+20 | | 6x-12=5x-20 | | 3ax-6x-ay+2y= | | 10x+6y=4 | | 32m+24= | | 16a^2b-24a^4b^2c= | | (6x+15)=(3x+21) | | 2x+114=6x-3.4 | | 3x-30=2x-8 | | (8m/m-4)-(32/m-4) | | 2x^2-3x^3= | | 3y-6y= | | w=1.8d+16.44 | | (4x-1)/(2x-1) | | 5(9)-28+y=180 | | 2x-4=x+0 | | 4x-1/2x-1 | | 3x-3.3=5x-5.3 | | 5(9)-18+y=180 | | 7+12x=106+1x | | 16x^2+36x=24 |